2020
DOI: 10.3389/fmicb.2020.547108
|View full text |Cite
|
Sign up to set email alerts
|

Symbiont-Mediated Insecticide Detoxification as an Emerging Problem in Insect Pests

Abstract: Pesticide use is prevalent with applications from the backyard gardener to large-scale agriculture and combatting pests in homes and industrial settings. Alongside the need to control unwanted pests comes the selective pressure generated by sustained pesticide use has become a concern leading to environmental contamination, pest resistance, and, thus, reduced pesticide efficacy. Despite efforts to improve the environmental impact and reduce off-target effects, chemical pesticides are relied on and control fail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(36 citation statements)
references
References 71 publications
1
34
0
1
Order By: Relevance
“…Given that spraying fenitrothion can enhance the abundance of fenitrothion-degrading Burkholderia strains in Riptortus pedestris gut ( Kikuchi et al, 2012 ), the high level of W. confusa in the migratory locust gut is probably the consequence of the increased amount of pesticides or other stresses affecting the migratory locust. These results further indicated that the sustainable management of major insect pests need to consider the role of gut microbiota ( Blanton and Peterson, 2020 ).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Given that spraying fenitrothion can enhance the abundance of fenitrothion-degrading Burkholderia strains in Riptortus pedestris gut ( Kikuchi et al, 2012 ), the high level of W. confusa in the migratory locust gut is probably the consequence of the increased amount of pesticides or other stresses affecting the migratory locust. These results further indicated that the sustainable management of major insect pests need to consider the role of gut microbiota ( Blanton and Peterson, 2020 ).…”
Section: Discussionmentioning
confidence: 94%
“…Some insect pests possessed insecticide resistance for bacteria-mediated degradation ( Itoh et al, 2018 ; Blanton and Peterson, 2020 ). Exploring the dominant gut bacteria and its potential functions will be helpful in pesticide development, pest management strategies, and pesticide bioremediation.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, compared with Hamiltonella- free aphid clones, Hamiltonella -infected aphid clones exhibit lower sensitivity to most of the tested insecticides at low concentrations ( 27 ). More generally, although the mechanisms of resistance to insecticides are diversified, detoxification from insecticides mediated by symbionts within insect pests and vectors is a trend that has now become clear and that is configured as an emerging problem in the control of these insects ( 28 ).…”
Section: Resultsmentioning
confidence: 99%
“…In fact, compared with Hamiltonella-free aphid clones, Hamiltonella- infected aphid clones exhibit lower sensitivity to most of the tested insecticides at low concentrations (27). More generally, although the mechanisms of resistance to insecticides are diversified, detoxification from insecticides mediated by symbionts within insect pests and vectors is a trend that has now become clear, and which is configured as an emerging problem in control of these insects (28).…”
Section: Resultsmentioning
confidence: 99%